Lipemia retinalis following FLAG-Ida protocol in an 11-year-old patient with acute myeloid leukemia - Kaplan Koruk, Reyhan Hazal; Kocabora, Mehmet Selim; Karaman Erdur, Sevil; Yaman, Yöntem (My University, 2025)
Introduction: We report a case of early-onset lipemia retinalis secondary to the FLAG-Ida protocol in the treatment of acute myeloid leukemia (AML) in an 11-year-old girl. Case Report: An 11-year-old patient, diagnosed with AML at four months old, experienced a relapse and was treated with the FLAG-Ida protocol (fludarabine, idarubicin, granulocyte-colony stimulating factor, and high-dose cytarabine). Prior to allogeneic stem cell transplantation, she underwent a pre-transplantation eye examination. The patient exhibited normal visual acuity in both eyes. Fundus examination revealed cream-white retinal vessels and a salmon-pink retina, indicative of grade 3 lipemia retinalis. Laboratory tests, normal before treatment initiation, showed significantly elevated serum cholesterol (727.6 mg/dL) and triglyceride (6015.6 mg/dL) levels post-treatment. After receiving fenofibrate, these levels decreased markedly, and the retinal vessels normalized on follow-up fundus examination. Conclusion: Lipemia retinalis, characterized by creamy-white retinal vessels resulting from hypertriglyceridemia, can develop as a secondary condition to chemotherapy. Early detection and treatment of hyperlipidemia are crucial to prevent severe ocular and systemic complications. This case highlights the importance of monitoring lipid levels and conducting thorough ophthalmologic examinations in patients undergoing chemotherapy.
Keywords: Pharmacology; Hypercholesterolemia; Hypertriglyceridemia; Leukemia